(untitled) (FUDMA JOURNAL OF SCIENCES, 2020)
The failure to adequately address farmers’ perception in soil studies have been identified as a limiting factor against the prospect of full realization of benefits of some soil related studies. This study was carried out in an area located between latitudes11° 02 ′ 00 ′′ N, 11° 3 ′ 43′ N, and longitudes 08° 41′ 35 ′′ E, 08° 57 ′ 06 ′′ along River Challawa, Kano State, Nigeria. Seven of farmers were first identified and then respondents were selected using simple random sampling technique. Structured questionnaires were collected from sixty Fadama farmers. The data was analysed by the used of tables, percentage and kruskal wallis’ test. The result for the socio-economic analysis shows that 25% were aged 36 to 40 (56 as their mean) years. There were 86.7% males against 13.3% females Fadama farmers in the area. The mean income of the farmers was found to be N. On fertility dynamics, 68.4% were of the view that fertility levels were not fixed, rather fertility indicators were variable. Also, 83.3% of the respondents indicated that soil fertility problems could be overcome through the practice of bush fallowing. Similarly, 81% of the farmers suggested that fertility could be best tackled when organic and inorganic fertilizer were applied simultaneously. Late growth and maturity of crops were the major indicators of fertility decrease according to 33.3% of the respondents. Finally, the study recommends creating more avenues for the education of the local farmers, training and retraining and creation of bioorganic fertilizer production plants.